Complex approach to implementation concept of «Ecological hotel» - Poyasnyk, Oksana; Bloshchinska (Dudkina), Olena; Ishchenko, Tatiana; Shydlovska, Olena; Dotsenko, Viktor (Complex approach to implementation concept of «Ecological hotel» / O. Y. Poyasnyk, O. O. Dudkina, T. I. Ishchenko, O. B. Shydlovska, V. F. Dotsenko // Nauka i Studia. – Przemysl: Nauka i Studia, 2015. – № 16 (147). – P. 30–37., 2015)
In article reviewed the modern approaches to the use of ecotechnologies in the hotel industry. Reveals the prerequisites for the development of ukrainian eco-hotel business. Grounded the possibility and expediency of building of eco-hotel with complex of innovative resource-saving and environmental protection technologies in the Lviv region.
Keywords: концепція; концепция; concept; екологічний готель; экологический отель; ecological hotel; екотехнології; экотехнологии; environmental technology; електрокотел; электрокотел; electric boiler; кафедра готельно-ресторанної справи